2018
DOI: 10.1080/21870764.2018.1446465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and aging temperature on the phosphorus removal properties of layered hydroxide synthesized from zinc acetate

Abstract: Zinc hydroxide acetate (ZHA) is a promising material for anion exchange applications because it has a layered structure with intercalating CH 3 COO − and H 2 O. ZHA can be synthesized through a direct precipitation method by adding sodium hydroxide solution to a Zn(OCOCH 3) 2 solution. In this study, ZHAs were synthesized under various conditions and tested as phosphorous removal agents. The ZHA precipitates were obtained at pH 6, 7, and 9. They were then aged at 25°C, 60°C, 90°C, and 120°C under hydrothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The endothermic process at 60-90°C is associated with about 8% weight loss, and the process at 110-150°C is associated with approximately 10% weight loss. This combined weight loss of 17-18% is close to the theoretical weight loss (17.5%) ascribed to the release of six water molecules from the formula unit, and the two associated reactions can be described by reaction formulae (1) and (2) [18,20]:…”
Section: Synthesis Of Zhassupporting
confidence: 72%
See 4 more Smart Citations
“…The endothermic process at 60-90°C is associated with about 8% weight loss, and the process at 110-150°C is associated with approximately 10% weight loss. This combined weight loss of 17-18% is close to the theoretical weight loss (17.5%) ascribed to the release of six water molecules from the formula unit, and the two associated reactions can be described by reaction formulae (1) and (2) [18,20]:…”
Section: Synthesis Of Zhassupporting
confidence: 72%
“…The thermal decomposition of Zn(OCOCH 3 ) 2 occurs at over 147°C, but the processes involved after reaction (2) are not straightforward. The decomposition of Zn(OCOCH 3 ) 2 upon heating is sensitive to the humidity of the surrounding atmosphere [18,20]. In this study, the weight loss observed by TG between 147 and 200°C can be mainly assigned to the processes that form ZnO through reaction (3).…”
Section: Synthesis Of Zhasmentioning
confidence: 70%
See 3 more Smart Citations